Valve embolization during transcatheter aortic valve implantation: Incidence, risk factors and follow-up by computed tomography - Frumkin, David; Pietron, Malte; Kind, Andreas; Brand, Anna; Knebel, Fabian; Laule, Michael; Leistner, David M.; Landmesser, Ulf; Krackhardt, Florian; Sherif, Mohammad; Sündermann, Simon H.; Grubitzsch, Herko; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background In most cases of transcatheter valve embolization and migration (TVEM), the embolized valve remains in the aorta after implantation of a second valve into the aortic root. There is little data on potential late complications such as valve thrombosis or aortic wall alterations by embolized valves. Aims The aim of this study was to analyze the incidence of TVEM in a large cohort of patients undergoing transcatheter aortic valve implantation (TAVI) and to examine embolized valves by computed tomography (CT) late after TAVI. Methods The patient database of our center was screened for cases of TVEM between July 2009 and July 2021. To identify risk factors, TVEM cases were compared to a cohort of 200 consecutive TAVI cases. Out of 35 surviving TVEM patients, ten patients underwent follow-up by echocardiography and CT. Results 54 TVEM occurred in 3757 TAVI procedures, 46 cases were managed percutaneously. Horizontal aorta (odds ratio [OR] 7.51, 95% confidence interval [CI] 3.4–16.6, p < 0.001), implantation of a self-expanding valve (OR 4.63, 95% CI 2.2–9.7, p < 0.01) and a left ventricular ejection fraction < 40% (OR 2.94, 95% CI 1.1–7.3, p = 0.016) were identified as risk factors for TVEM. CT scans were performed on average 26.3 months after TAVI (range 2–84 months) and detected hypoattenuated leaflet thickening (HALT) in two patients as well as parts of the stent frame protruding into the aortic wall in three patients. Conclusion TVEM represents a rare complication of TAVI. Follow up-CT detected no pathological findings requiring intervention.